2020
DOI: 10.3390/life10050053
|View full text |Cite
|
Sign up to set email alerts
|

A New Record for Microbial Perchlorate Tolerance: Fungal Growth in NaClO4 Brines and its Implications for Putative Life on Mars

Abstract: The habitability of Mars is strongly dependent on the availability of liquid water, which is essential for life as we know it. One of the few places where liquid water might be found on Mars is in liquid perchlorate brines that could form via deliquescence. As these concentrated perchlorate salt solutions do not occur on Earth as natural environments, it is necessary to investigate in lab experiments the potential of these brines to serve as a microbial habitat. Here, we report on the sodium perchlorate (NaClO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…For example, halophilic Archaea of the family Halobacteriaceae and Halomonas elongata showed a weak growth in 600 mM Na-perchlorate (Oren et al ., 2014), the growth of the archaeon Halorubrum lacusprofundi was still measurable in 800 mM perchlorate ions (Laye and DasSarma, 2018), while Hydrogenothermus marinus did not replicate in 400 mM Na-perchlorate (Beblo-Vranesevic et al ., 2017). So far the highest perchlorate tolerance was reported for the yeast Debaryomyces hansenii growing in 2.4 M Na-perchlorate (Heinz et al ., 2020), a value twice that of the bacterium Planococcus halocryophilus (Heinz et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, halophilic Archaea of the family Halobacteriaceae and Halomonas elongata showed a weak growth in 600 mM Na-perchlorate (Oren et al ., 2014), the growth of the archaeon Halorubrum lacusprofundi was still measurable in 800 mM perchlorate ions (Laye and DasSarma, 2018), while Hydrogenothermus marinus did not replicate in 400 mM Na-perchlorate (Beblo-Vranesevic et al ., 2017). So far the highest perchlorate tolerance was reported for the yeast Debaryomyces hansenii growing in 2.4 M Na-perchlorate (Heinz et al ., 2020), a value twice that of the bacterium Planococcus halocryophilus (Heinz et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about the microbial toxicity of dissolved perchlorate ions. In fact, dissimilatory perchlorate reduction is a common metabolic pathway in bacteria (Bardiya and Bae, 2011) and archaea (Liebensteiner et al, 2013), and perchlorate can be tolerated in high concentrations by eukaryotes, e.g., the halotolerant yeast Debaryomyces hansenii can tolerate 2.4 M NaClO 4 (Heinz et al, 2020). Furthermore, dissolved perchlorate ions are relatively inert and non-oxidizing due to kinetic barriers (Urbansky, 1998).…”
Section: Non-physicochemical Effectsmentioning
confidence: 99%
“…Furthermore, it has the highest bacterial perchlorate tolerance (13.6 wt/vol% NaClO 4 at +25 • C) reported to date (Heinz et al, 2019). Only some fungi are known to tolerate higher perchlorate concentrations (Heinz et al, 2020). Hence, this halo-and cryotolerant organism is highly suitable as a model organism for studying the habitability of Martian cryobrines and was therefore used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that halophilic bacteria, isolated from various saline natural environments, have the ability to reproduce on culture media containing 1% perchlorate mixture simulating the composition of Mars regolith (Al Soudi et al ., 2017). The growth of halotolerant bacteria Halomonas venusta and Planococcus halocryophilus has been shown on liquid media containing 12.2 and 13.6% sodium perchlorate, respectively (Al Soudi et al ., 2017; Heinz et al ., 2019, 2020). It has been demonstrated that bacteria could develop on media simulating the salt composition of Martian soil containing perchlorates at a concentration of 0.5% (Nicholson et al ., 2012), in brines containing a mixture of sulphates and perchlorates with a concentration of the latter up to 3.7% (Beblo-Vranesevic et al ., 2017 b ), as well as maintain viability after short-term (15 min) exposure to sodium perchlorate with concentration up to 43% (Beblo-Vranesevic et al ., 2017 a , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the maximum concentration of sodium perchlorate which allows microbial cells proliferation in vitro is considered to be 9.8% for Archaea ( Halorubrum lacusprofundi ), 13.6% for Bacteria ( P. halocryophilus ) and 29.9% for micromycetes ( Debaryomyces hansenii ) (Heinz et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%